FORMATION IN CLOTHING DESIGN: HISTORICAL RECONSTRUCTION AND MODERN COMPOSITION SOLUTIONS OF CORSETS AND CRINOLINES - КОКОРІНА, Г. В.; ДАВИДЕНКО, І. В.; ЧУБОТІНА, І. М.; ГЕРАСИМЕНКО, О. Д. (Art and Design, 2023)
The purpose of the article is to present the results of scientific and practical work on the reconstruction of historical forms of corsets and crinolines, which is conducted at the department of art and costume design of KNUTD, as well as to substantiate the relevance of frame products in modern clothing design. The work is based on methods of systematization of visual sources from the history of fashion, as well as methods of historical-chronological and comparative analysis. In the course of experimental research, methods of practical reconstruction of historical clothing, means of projection of a three-dimensional shape on a plane and the method of approximation were used. The evolution of the development of frame forms of clothing in the European fashion of the 16th-19th centuries, the functional and aesthetic significance of corsets and crinolines at different stages of the history of the costume are analyzed. The experience of reproducing samples of historical clothing at the department of art and costume design of KNUTD is described, the significance of such an approach for the professional training of clothing designers is analyzed. The article also presents an overview of the use of the theme of corsets and crinolines in the work of prominent designers of the late 20th and early 21st centuries, and substantiates the actualization of this theme in the collections of 2023. The article is illustrated with original photographs from the department's archive, most of which are being published for the first time. The scientific novelty of the work consists in the scientific generalization of the results of the practical reconstruction of the frame forms of historical clothing in the context of the actualization of corsets and crinolines in modern costume design. The practical significance of the study is related to the adaptation of the approximation method to the tasks of analyzing the geometric form of the historical costume of the XVI–XIX centuries, taking into account the evolution of the frame elements of clothing. Practical work on the reconstruction of clothes can be involved in the process of designing new modern collections.